Galectins - Cummings, Richard D. (2022)
Galectins are among the most widely expressed class of lectins in all organisms. They typically bind β-galactose-containing glycoconjugates and share primary structural homology in their carbohydrate-recognition domains (CRDs). Galectins have many biological functions, including roles in development, regulation of immune cell activities, and microbial recognition as part of the innate immune system. This chapter describes the diversity of the galectin family and presents an overview of what is known about their biosynthesis, secretion, and biological roles.